A dispute about Gender-sensitive Language in Serbian Law - Ćorić, Dragana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
gender-sensitive language is considered as one of products of the heroic struggle of women to be recognized and respected in modern world, for all what they are and for all what they could be and could achieve. This means that women are not escaping from their natural, biological roles -especially mother’s role and other cherishing, nurturing and gentle emotions they have and use in raising the children and keeping the family on the same spot. This means that it should make men to find them, on linguistical and more over on other levels, equally capable of doing all sorts of jobs they are doing themselves. The newly changed national legal framework makes use of gender sensitive language as obligation since May 2024. All governmental bodies, on any territorial level, journalists, children and teachers at schools etc. will be obligated to use those gender sensitive terms , especially when they are used to mark woman in special profession(for example, in judiciary, in area of national security and defense, etc.) or else  will be fined.In this paper the author will deal shortly with both argumentations-pro and contra of using gender sensitive language, and also to present own opinion- which is in the middle. Also, it will be presented one of the disputes in area of protection of human rights. The dispute is about whether all protectors of citizens’ rights should be called-ombudsman, as the original name of this institution is, or ombudswoman, when marking the woman who serves on this position, or ombudsperson-as gender neutral, or else.
Keywords: gender, sex, gender-sensitive language, disputes